Umbilical Artery Doppler Measurements in Last Week of Pregnancy and Correlation with Vitality of Newborn Lambs - Brenner Busch, Ana Paula; Smaniotto Compagnoni, Isabelle; Francisco da Cruz Filho, Guilherme; Ilha Borges, Luiza; Rodrigues dos Santos, João Gabriel; Laskoski, Luciane Maria; Muehlbauer, Eloisa; Gomes Monteiro, Alda Lucia; Rodrigues Froes, Tilde (Acta Scientiae Veterinariae, 2023)
Background: There is a high lamb mortality rate during the first 3 days of life, resulting in sheep flock economic losses and neonate welfare concerns. A significant number of neonatal deaths could be avoided by preventive management, early diagnosis, and consequently well-timed intervention. The aim of the study was to evaluate the use of umbilical artery Doppler to predict the vitality score (APGAR) of lambs at birth, and its use as a screening tool for detecting high-risk neonatal cases in the last week of gestation, describing changes in the resistivity and pulsatility index in singletons and twins. Materials, Methods & Results: A total of 27 White Dorper pregnant ewes were studied: 19 multiparous (ewes, 2 to 4-years-old) and 8 primiparous (yearling, up to 1-year-old). From 130 days of pregnancy, gestational ultrasound was performed weekly until delivery, but only data from the last pre-partum scan for each ewe was included. The inclusion criteria for the analysis of the umbilical arteries Doppler were the positioning of the fetus and the quality of the images obtained. Identification of each of the twin fetuses after birth was performed by reference to ultrasound fetometry and its correlation with birth weight. The vitality score at birth (APGAR) was used to classify each group, regardless of the characteristic of eutocic or dystocic delivery, with Group 1 lambs having normal vitality (APGAR ≥ 7) and Group 2 lambs having low vitality (APGAR < 7). A transabdominal Doppler ultrasound of 28 fetal umbilical arteries was performed in the last week before delivery (146 ± 2.4 days of gestation), and the results were compared with the vitality scores of lambs at birth. There were 53.6% of lambs (15/28) with normal vitality scores (Group 1), and 46.4% of lambs (13/28) had low vitality scores (Group 2). The umbilical artery Doppler ultrasound analyzes of the resistance index (RI), the pulsatility index (PI), and the RI and PI oscillations determined by the resistivity index gradient (RIgrad), the resistivity index variations (RIvar%), the pulsatility index gradient (PIgrad) and the pulsatility index variation (PIvar%) were established for each fetus. Pearson’s correlation was performed for each umbilical artery Doppler ultrasound variable and vitality score of each lamb, and the T Student’s test was performed between Groups 1 and 2. There were no statistically significant differences between groups. Furthermore, the RI values or oscillations did not correlate with the lambs’ vitality score, and mildly increased PI values need to be interpreted with caution. Neonatal vitality in lambs was correlated with pulsatility index oscillations: PIgrad (r = 0.4005; P = 0.0346) and PIvar% (r = 007; P = 0.0299). Discussion: Measurement of umbilical artery RI and PI is possible in ewes with singleton and twin pregnancies in the last week of gestation. High PI of the umbilical artery did not correlate with a low lamb vitality score at birth, as previously described in human fetal medicine. The PI alone cannot be correlated with APGAR in lambs, but the PIgrad and PIvar% analyzes should be performed. In conclusion, the RI and PI values, if analyzed in isolation, show no correlation with the vitality scores of lambs at birth. However, making multiple measurements to derive associations between maximum and minimum values of PI such as PIgrad and PIvar% in the same fetus, could help to screen for high-risk neonates. Keywords: sheep, ultrasound, neonatal risk, Apgar.